THE VALUE EDUCATION OF QOSIDAH BURDAH ARTS IN BOARDING SCHOOL IN THE LAND OF SUNDA - sulasman ujang (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
Burdah Al-Bushiri contains a string of poems of praise to the Prophet Muhammad. Burdah is a literary work of Sharafuddin Abu Abdillah Muhammad Ibn Zaid Al Bushiri.Burdah Al-Bushiri widely taught in boarding school. Boarding School teaches a lot of Value educations. Value educations contained in Burdah Al-Bushiri be internalized through the medium of art, the art of Qosidah Burdah. This article aims to explain values contained in Qosidah Burdah. To explain this purpose, used literature. Thus, we will know about values of educationcontained in Qosidah Burdah. The results showed that Values contained in Qosidah Burdah has affected the attitude and character of students at the boarding school. Boarding School has been instrumental in instilling the values of theological, juridical, socio-cultural Islam, and Sufi values contained in Art Qosidah Burdah. Sufistic value of Qosidah Burdah in boarding implanted with the aim to cleanse the heart from all impurities soul. Values contained in Qosidah Burdah among others about repentance, asceticism, patience, sincerity, trust, and mahabbah. To give meaning passion in poetry Qosidah Burdah and soul enlightenment for students at the school, then do internalization of sufistic values from Qosidah Burdah through the art of music. Burdah Qosidah Music Arts at the school in addition is also used as a tool to improve and help the personal and social students